2011
DOI: 10.1109/tasc.2010.2093491
|View full text |Cite
|
Sign up to set email alerts
|

Quench Behavior and Protection in Cryocooler-Cooled YBCO Pancake Coil for SMES

Abstract: The thermal behavior of a high-temperature superconducting (HTS) coil is significantly different from that of lowtemperature superconducting (LTS) coil because it has a greater volumetric heat capacity at the temperature required for practical use. Therefore, the possibility of quench in HTS coils is much lower than that in LTS coils. In the application of the YBCO coil to Superconducting Magnetic Energy Storage (SMES) system, electrical charging and discharging are repeated; therefore, the superconducting cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Therefore, a quench must be detected using some other method. In the previous paper, we showed that a quench in the coil could be detected by observing the transposition of the current in the bundle conductor caused by local normal transition [5]. After a quench is detected by observing a non-uniform current, the stored energy of the coil is dumped on the external resistance.…”
Section: B Quench Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a quench must be detected using some other method. In the previous paper, we showed that a quench in the coil could be detected by observing the transposition of the current in the bundle conductor caused by local normal transition [5]. After a quench is detected by observing a non-uniform current, the stored energy of the coil is dumped on the external resistance.…”
Section: B Quench Detectionmentioning
confidence: 99%
“…Moreover, we have investigated the redistribution characteristics of the transport current in, and the thermal behavior of, a coil wound during a quench and discussed a quench detection method by observing a non-uniform current in the coil [4], [5]. In this paper, based on these studies, we investigate the transposition of the current and the thermal behavior during a dump and determine the appropriate stabilizer thickness for the YBCO-coated conductors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the inductance of a PWNI coil is significantly decreased with the reduced number of turns compared with a single-wound NI coil (SWNI) of identical size, the charging delay can be significantly suppressed [37,38]. Some studies have used numerical simulation methods to analyze the external electromagnetic characteristics of PWNI coils, such as central magnetic field and coil voltage [39][40][41]. The azimuthal current distribution among different turns in PWNI coils at certain times has been analyzed by the circuit network model [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…However, the initiation of thermal runaway in multifilament coated conductors has not been experimentally studied. Furthermore, previous experimental studies on thermal runaway did not directly discuss the conditions under which the conventional quench detection and protection scheme (i.e., detecting quench/thermal runaway using voltage taps and dumping the stored energy in an external dump resistor) could be applied [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%